2012
DOI: 10.1016/j.archger.2011.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Perception and negative effect of loneliness in a Chicago Chinese population of older adults

Abstract: This qualitative study aims to investigate the cultural understandings of loneliness, identify the contexts of loneliness, and to examine its effect on the health and well-being of U.S. Chinese older adults. Despite loneliness is one of the main indicators of well-being, little attention has been paid to understanding loneliness among immigrant older adults. This study utilizes both survey questionnaires and semi-structured focus group methods to investigate the feelings of loneliness among U.S. Chinese older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
103
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 44 publications
9
103
0
1
Order By: Relevance
“…[20] In a qualitative study on loneliness among U.S. Chinese older adults, "children don't visit their parents" was described as "the worst scenario" of loneliness. [30] While it is noted that lack of companionship is the most prevalent loneliness symptom among the U.S. Chinese older adults due to the family-oriented cultural value, [27] our finding furthermore supports the idea that filial piety is an important cultural value that influences intergenerational relationships and thus, affects the psychological well-being of older adults. Future study with mixed research methodology is needed to explore the underlying mechanism to understand how perceived filial piety receipt influences the severity of loneliness.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…[20] In a qualitative study on loneliness among U.S. Chinese older adults, "children don't visit their parents" was described as "the worst scenario" of loneliness. [30] While it is noted that lack of companionship is the most prevalent loneliness symptom among the U.S. Chinese older adults due to the family-oriented cultural value, [27] our finding furthermore supports the idea that filial piety is an important cultural value that influences intergenerational relationships and thus, affects the psychological well-being of older adults. Future study with mixed research methodology is needed to explore the underlying mechanism to understand how perceived filial piety receipt influences the severity of loneliness.…”
supporting
confidence: 73%
“…[29] A qualitative study found that a majority of U.S. Chinese older adults attributed loneliness to the absence of satisfying intergeneralization relationships, [30] calling for more research attention to set up quantitative associations between filial piety and loneliness. A better understanding of this issue can contribute to the detection of loneliness and provide suggestions for interventions geared towards reducing loneliness among the Chinese community in a culturally-sensitive approach.…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness occurs in varying intensities and encompasses various circumstances and causes (Heinrich & Gullone, 2006). The intense feeling of being empty, being in a state of being left behind, and being in grief is the manifestation of loneliness (Dong, Chang, Wong, & Simon, 2012). Loneliness is a sense of distance from others, low relational value, and lack of friendship (Dong et al, 2012, p.151).…”
Section: Definitionmentioning
confidence: 99%
“…Weiss divides loneliness into two forms, social loneliness and emotional loneliness (Dong et al, 2012). Emotional loneliness is a very painful form of isolation.…”
Section: Form Of Lonelinessmentioning
confidence: 99%
“…Loneliness is experienced in every stage of the lifespan, even in 5-year-old children [9]. Loneliness afects both young people (e.g., [8,10,11]) and older migrants (e.g., [12,13]). For individuals in Western societies, loneliness seems to follow a U-shaped distribution, whereby adolescents/young adults (<25 years old) and older adults (>65 years old) have higher rates of loneliness than adults in the middle-age spectrum [7].…”
Section: Introductionmentioning
confidence: 99%